Wpływ jednolitego rynku europejskiego na dobrobyt (ujęcie teoretyczne) - Czarny, Elżbieta; Rusinowska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents how the existence of single market causes that the welfare level is increasing. The presented model is a simplification of the complex reality of European integration. The authors focus on the impact of prices standardization on the welfare level. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 91-101